Шевченківська тема у спадщині історика й педагога Миколи Володимировича Стороженка (1861—1944) - Харчук, Р. (Слово і Час, 2020)
У статті розглянуто шевченківську тему у спогадах Миколи Володимировича Стороженка «З мого життя» і в його листах до П. Куліша. Авторка вважає, що зазначена тема була для історика принагідною, а його ставлення до поета амбівалентним. Особливу увагу вона звертає на проблему авторства публікації «Эпизод из жизни Т. Шевченка», яку з огляду на криптонім С-ко дослідники нині приписують Миколі Володимировичу Стороженкові. Хоч авторство Миколи — найвірогідніше, проте у статті викладено й аргументи на користь авторствайого брата, Андрія Володимировича Стороженка. Останній підписував свої публікації криптонімом С-ко, А. Андрій Стороженко цікавився мистецькою спадщиною Шевченка й давніми портретами. У статті «Эпизод из жизни Т. Шевченка» йдеться про втрачений портрет пані Шостки. Андрій Стороженко розумів значення поета для української ідеї, але заперечував право українців на самовизначення, тому у праці «Український рух», що її й досі використовує російська пропаганда в боротьбі з «українським сепаратизмом», вивів карикатурну постать Шевченка. Імпульсом до створення цієї карикатури послужила Кулішева теза про неосвіченість Шевченка і його «полупьяную музу». The paper deals with Shevchenko’s theme in Mykola Storozhenko’s memoirs “From My Life” and in his letters to Panteleimon Kulish. The author of the paper believes that this issue was marginal for the historian, as Storozhenko’s attitude towards the poet was ambivalent. Aft er all, in articles on historical issues, Mykola Storozhenko quoted Shevchenko only once without giving his name. Special attention is paid to the authorship of the paper “An Episode from the Life of T. Shevchenko”, which researchers now attribute to Mykola Storozhenko based on the signature ‘С-кo’. It is noteworthy that he did not mention this episode in his memoirs, writing about dance evenings in Moisivka, as well as in the publication about his grandmother Maria Korsun. While Mykola’s authorship is the most probable, there are some arguments in favor of his brother’s authorship. Andrii Storozhenko signed his publications with the signature ‘C-кo, A.’. He was interested in Shevchenko’s artistic heritage, ancient portraits and understood the importance of Shevchenko for the Ukrainian idea, despite the fact of creating the caricature character of the poet in his work “The Ukrainian Movement”, which is still used by Russian propaganda in its fight against the ‘Ukrainian separatism’. The article also deals with the problem of perceiving Shevchenko as a natural talent without proper education. It is evidenced by the letter of Mykola Storozhenko tо Panteleimon Kulish. The author is inclined to explain the vitality of the thesis about the poet’s ignorance and poor literacy by the dual Russian-Ukrainian identity which was widespread among the contemporary intellectuals of Dnieper Ukraine and rooted in their sense of inferiority.